772 Gap analysis on pesticides control and occupational health legislation in the united arab emirates. (1st September 2016) - Dhaheri, Hamda Al; Loney, Tom; Aw, Tar-Ching; Adem, Abdu; Adam, Balazs; Elias, Anza; Grivna, Michal; Blair, Iain
Abstract : Background: The United Arab Emirates (UAE) is one of the leading agricultural producers in the Middle East, particularly for date fruit cultivation. Federal and local agencies are responsible for governing occupational health and safety regulations across the seven emirates. A gap analysis was performed on specific UAE legislation related to the safe use of pesticides compared to a compliance checklist developed from international best practice. Interviews with municipalities, authorities, and industry representatives were used to collect the data required in the checklist. Description of the problem: The UAE Ministry of Environment and Water reported that the average amount of pesticides used in the UAE in 2013 was five to ten times higher than in India, Europe, and the United States. Sixty-percent of UAE expatriate workers ( 5.5 million) are unskilled migrants from less-developed countries with low education and literacy rates (39% educated only to primary level or less). Agricultural workers lack any job-specific training and may not understand instructions on handling chemicals or pesticides safely which places them at a high risk of occupational exposure. Results: The UAE Ministry of Labour only stipulates broad federal occupational health regulations for worker protection and residency visa screening obligations for employers. There are no specific articles related to the control of hazardous chemicals such as pesticides. At the local level, only Abu Dhabi and Dubai emirates provide guidelines related to occupational specific chemical exposures; however, there is currently limited evidence of application and enforcement. Conclusions: Currently, there is inter-emirate fragmentation in the scope and enforcement of regulations related to the use and control of chemicals such as pesticides. Future legislation should include job-specific training, implementation of effective chemical hazard control methods, and health surveillance of workers exposed to pesticides.